Robust PID and Fractional PI Controllers Tuning for General Plant Model - Jasim., Dr. Basil H. (Basrah Journal for Engineering Sciences, 2015)
In this paper, a design procedure which assumes general integer or noninteger order plant models ‘also can be unknown’ has been adopted to tune PID and fractional order PI (FOPI) controller. The design procedure depends on some specifications of frequency response of open loop system to ensure performance and robustness of step response of closed loop system. Firstly, the procedure is applied to integer order conventional PID (IOPID) controller, and then it has been extended to FOPI. Extensive simulation study has been made to investigate the performance of the obtained controllers, and also to compare between the two controllers. The simulation study has showed the validity and that the proposed controllers have good features in all of control demands, where it shows that these controllers have fast rise time with no overshoot and negligible steady state error. Also, it has showed that FOPI controller performs better than IOPID one.